Merging Application Models in a MDA Based Runtime Environment for Enterprise Information Systems - Davis, Jon; Tierney, Andrew; Chang, Elizabeth (IEEE, 2005)
The issue of merging source code based applications is very problematic, particularly when involving code from disparate sources, due to the typical unsuitability of available source code for software merging. The relatively recent field of model driven architecture is primely involved in the definition and development of the source model structures for model based applications and in developing transformations from the abstract models to various executable formats. The authors are also involved in these MDA activities in the development of their G2 prototype system targeted at the specific domain of enterprise information system style applications. They have reviewed various methods for merging application models within this domain and describe the fundamentals of three application model integration methods from their G2 system; standard element referencing, virtual data element mapping and element envelopment that can be used to provide practical and simple application model merging at both the design time and runtime of a model based production system, to produce a working integrated merged application.